Degradation of patulin and effect of flavor component in apple juice by glow discharge plasma (GDP) - LI Zhaodi; WANG Ting; LI Wan; TANG Hongsheng; LONG Haitao; XU Weibing; PU Lumei (Fushe yanjiu yu fushe gongyi xuebao, 2023)
Patulin is the most common mycotoxins present in apple juice, and is very harmful to consumer health and economic development. Herein, we investigated the degradation of patulin and promotion of flavor component in apple juice by glow discharge plasma (GDP). The results showed that when the DC voltage was 550 V and the current range was 10-90 mA, the degradation rate of Patulin in apple juice reached 92.89% after treatment by glow discharge plasma for 15 min. After 30 min of GDP treatment, no significant change in the soluble solids and phenols of apple juice was observed, while the electrical conductivity, redox potential, and the color value of apple juice increased, with a slight decrease in pH. After 20 min of GDP treatment, 38 compounds were detected in apple juice by gas chromatography and mass spectrometry (GC-MS), including 8 esters, 7 alcohols, 20 aldehydes and ketones, and 3 others. Two new components ,viz. acetophenone and 6,10-dimethyl-5,9-undeundene-2-one were detected compared with the control; both are sweet and fragrant essential oils, which could make the apple juice taste more delicious. The results of this study can provide the basis for applying GDP in the degradation of patulin and promotion of flavor components in apple juice.